If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = 2z + 10 Reorder the terms: -6 + 3x = 2z + 10 Reorder the terms: -6 + 3x = 10 + 2z Solving -6 + 3x = 10 + 2z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = 10 + 6 + 2z Combine like terms: -6 + 6 = 0 0 + 3x = 10 + 6 + 2z 3x = 10 + 6 + 2z Combine like terms: 10 + 6 = 16 3x = 16 + 2z Divide each side by '3'. x = 5.333333333 + 0.6666666667z Simplifying x = 5.333333333 + 0.6666666667z
| 12x-y=1 | | 6x=63-x | | y/3-14=3 | | 3/5-2/5b=4/5b | | 6b-3b-2b=11 | | 5m^2+48m-20=0 | | 5(x-3)+5=3x+2(-4+x) | | X-3/7=-8 | | 89=4w+17 | | 13M-(8M+17)=23 | | -7+6x=7x-13 | | 5(2n+4)=8(5n+8)+4 | | -9x+10=-80 | | 3m-1/4g=H | | 3a-6b+27= | | 9w-3w-6w+3w+w=16 | | 13/22=7/x | | -10-b=-5b-6b | | 8(3n+1)=7(9n+4)+2 | | 3a-6b+27=0 | | 10p-4p=18 | | y(3y+2)+(y+3y^2)= | | 0.2=0.05d | | 7v-5v= | | 3x-7+2x+4=77 | | p=(11-2x)i+14j | | 5(3n+2)=6(7n+4)+7 | | 8q-6q=10 | | 2/7×=4 | | 1/5=1/20d | | 7y+2(y-5)=4(y+2)-2 | | 1/3(9-12x) |